Comparison of still image quality between traditional 35 mm digital and GoPro cameras in a surgical setting. (3rd July 2019) - Adin, C.; Royal, K.; Roe, S.; Mathews, K.; Risselada, M.; Scharf, V.
Abstract: Intraoperative photography is used to obtain images for both education and research purposes, but poses challenges due concerns regarding aseptic technique. Waterproof digital cameras have sterilisable cases that can be used by the surgeon for intraoperative photography. We compared the quality of still intraoperative images obtained by a non-scrubbed observer using a 35 mm single lens reflex (SLR) camera to images obtained by the surgeon using a GoPro camera in a sterilised case. Image quality was scored using a 4 point Likert scale by 3 groups of end users with differing experience: faculty surgeons, surgical residents, and 3rd year veterinary students. Mean ± SEM overall image quality scores were higher for the traditional 35 mm digital SLR camera when compared to the GoPro (3.25 ± 0.08 vs. 2.0 ± 0.08, p < .0001), as were scores for each image characteristic (brightness, colour, sharpness, and contrast). Image quality scores for each camera also differed significantly between user groups, with expert users (faculty and residents) giving lower quality scores when compared to scores from novices (students). Findings suggest that GoPro cameras provide lower intraoperative image quality than digital SLR cameras, although lower quality images may be more accepted by novices than by experienced users.